Pembuatan Emulsi Virgin Coconut Oil (VCO) Dengan Pulvis Gummi Arabici (PGA) Dan Uji Aktivitasnya Terhadap SGOT Dan SGPT pada Mencit Putih - Nori Wirahmi; Sonia Yuwana; Salman Umar (STIFARM Padang, 2009)
The research of the making of Virgin Coconut Oil emulsion with the Acasia and its activity test as a SGOT dan SGPT against white female mouse had been done. The liver damage was inducted using paracetamol doses 0.026 g/20g BB. The emulsion was made with dry gom method and evaluated in stability and VCO emulsion viscocity using a Viscometer Stomer. The parameter observed was the decreasing of SGOT and SGPT activities during giving 1, 3, 7 medicine. The result indicated that the emulsion VCO was stable using Acasia as emulsifying agent to 50°C during 6 hours and can be used as the decreasing SGOT and SGPT activities at observating on day 2, 4 and 8.